Effect of Treatment With Biologic Agents on the Novel Inflammatory Biomarkers Systemic Immune Inflammation Index and Systemic Inflammation Response Index for Psoriasis - Funda Tamer; Yusuf Can Edek; Ahmet Burhan Aksakal (Mattioli1885, 2024)
Introduction: Psoriasis is a chronic cutaneous disorder with underlying systemic inflammation. The systemic immune inflammation (SII) and systemic inflammation response indexes (SIRI) are novel biomarkers that indicate systemic inflammation. Objectives: We aimed to evaluate the effect of biological agent treatment on SII and SIRI in psoriasis patients. Methods: Between April 2019 and October 2022, SII and SIRI were retrospectively evaluated in patients with psoriasis before and three months after the initiation of biological agents. Results: This study included 220 patients, 101 females and 119 males. SIRI was significantly higher in male patients compared to females (P < 0.001). Although not statistically significant, SII and SIRI were higher in obese patients, patients with severe psoriasis, longer disease duration, nail involvement and patients who received previous biological agent treatment. SII was also higher in patients with hypertension, diabetes, hepatic steatosis, depression and coronary artery disease (P = 0.801, P = 0.752, P = 0.706, P = 0.079, P = 0.861, respectively), whereas SIRI was higher in patients with diabetes and depression (P = 0.263, P = 0.777, respectively). Both SII and SIRI statistically significantly decreased after treatment with adalimumab, infliximab, ixekizumab, secukinumab, ustekinumab and risankizumab. Conclusions: SII and SIRI may indicate the severity of psoriasis as well as SII may be associated with psoriatic arthritis, hypertension, hepatic steatosis and coronary artery disease in patients with psoriasis. There is no consensus on the biomarkers that can be used to create an optimized treatment strategy in psoriasis. Therefore, SII and SIRI may be helpful in making the choice of treatment and in the follow-up of patients with psoriasis treated with biological agents.